Syringeless Electrospinning toward Versatile Fabrication of Nanofiber Web - Moon, Seongjun (Sci Rep, 2017)
Although electrospinning is considered a powerful and generic tool for the preparation of nanofiber webs, several issues still need to be overcome for real-world applications. Most of these issues stem from the use of a syringe-based system, where the key factor influencing successful electrospinning is the maintenance of several subtle balances such as those of between the mass and the electrical state. It is extremely difficult to maintain these balances throughout the spinning process until all the polymeric solution in the syringe has been consumed. To overcome these limitations, we have developed a syringeless electrospinning technique as an alternative and efficient means of preparing a nanofiber web. This new technique uses a helically probed rotating cylinder. This technique can not only cover conventional methods, but also provides several advantages over syringe-based and needless electrospinning in terms of productivity (6 times higher) and processibility. For example, we can produce nanofibers with highly crystalline polymers and nanofiber-webs comprising networks of several different polymers, which is sometimes difficult in conventional electrospinning. In addition, this method provides several benefits for colloidal electrospinning as well. This method should help expand the range of applications for electrospun nanofiber webs in the near future.